What Makes Woman Afraid of Their Childbirth?: A Qualitative Study - Nurhidayati, Siti; Novika, Revi Gama Hatta; Wahidah, Nurul Jannatul; Sari, Atriany Nilam; Maulida, Luluk Fajria; Maulina, Rufidah; Habiba, Chusna; Anggi, Ramadhani (JURNAL INFO KESEHATAN, 2023)
Fear generally fills the minds of pregnant women as they enter the third trimester of gestation. The older the gestational age, the more attention and thoughts of pregnant women are drawn to the approaching climax of childbirth, intensifying their anxiety and fear. This study aimed to assess the knowledge of birth preparedness and fear of childbirth. A qualitative facility-based descriptive study design and client exit interview questionnaire were utilized, conducted in Primary Health Care Mondokan, Sragen, from April until June 2023 with 33 pregnant women. Study participants were selected through purposive sampling. Three categories highlighted the preparedness for childbirth, including finding primary sources of information, the importance of birth companions, and reminding about the natural process of childbirth. The fear of childbirth was associated with fear of the childbirth process, fear of the tools used during childbirth, and the condition of the unborn baby. The findings suggest that pregnant women should prepare for childbirth and increase their knowledge of delivery by participating in antenatal classes to reduce fear about the childbirth process. Therefore, family healthcare providers, health facilities, other partners, program-level managers, and policymakers must take responsibility for improving health education and increasing preparedness and complication readiness through easily accessible health education strategies.